Anaplastic lymphoma kinase inhibitors—a review of anticancer properties, clinical efficacy, and resistance mechanisms - Kiełbowski, Kajetan; Żychowska, Justyna; Becht, Rafał (Frontiers in Pharmacology, 2023)
Fusions and mutations of anaplastic lymphoma kinase (ALK), a tyrosine kinase receptor, have been identified in several neoplastic diseases. Rearranged ALK is a driver of tumorigenesis, which activates various signaling pathway associated with proliferation and survival. To date, several agents that target and inhibit ALK have been developed. The most studied ALK-positive disease is non-small cell lung cancer, and three generations of ALK tyrosine kinase inhibitors (TKIs) have been approved for the treatment of metastatic disease. Nevertheless, the use of ALK-TKIs is associated with acquired resistance (resistance mutations, bypass signaling), which leads to disease progression and may require a substitution or introduction of other treatment agents. Understanding of the complex nature and network of resistance mutations may allow to introduce sequential and targeted therapies. In this review, we aim to summarize the efficacy and safety profile of ALK inhibitors, describe off-target anticancer effects, and discuss resistance mechanisms in the context of personalized oncology.